2008
DOI: 10.1164/rccm.200708-1234oc
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Profile of New Bacterial Strain Exacerbations of Chronic Obstructive Pulmonary Disease

Abstract: Neutrophilic airway inflammation and systemic inflammation are more intense with well-defined bacterial exacerbations than with nonbacterial exacerbations. Clinical course of exacerbation and inflammation are closely linked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
143
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(153 citation statements)
references
References 34 publications
5
143
0
5
Order By: Relevance
“…When airway and systemic inflammation during new strain exacerbations are compared with exacerbations without new bacterial strains, a greater intensity of neutrophilic airway inflammation and systemic inflammation is demonstrated in the former group [15]. Furthermore, WHITE et al [16] have shown that clearance of bacteria following 10 days of treatment with antibiotics for purulent sputum exacerbations was associated with a reduction in neutrophilic inflammation, while bacterial persistence was associated with persistent elevation of airway inflammation.…”
Section: Mechanisms Of Bacterial Pathogenesis In Copdmentioning
confidence: 99%
“…When airway and systemic inflammation during new strain exacerbations are compared with exacerbations without new bacterial strains, a greater intensity of neutrophilic airway inflammation and systemic inflammation is demonstrated in the former group [15]. Furthermore, WHITE et al [16] have shown that clearance of bacteria following 10 days of treatment with antibiotics for purulent sputum exacerbations was associated with a reduction in neutrophilic inflammation, while bacterial persistence was associated with persistent elevation of airway inflammation.…”
Section: Mechanisms Of Bacterial Pathogenesis In Copdmentioning
confidence: 99%
“…Exacerbations are major drivers of morbidity, mortality, and health care use in chronic obstructive pulmonary disease (COPD) (1)(2)(3). Most exacerbations are triggered by bacterial or viral infections (4), or by acquisition of a new strain of a colonizing bacterium (1,2).…”
mentioning
confidence: 99%
“…Most exacerbations are triggered by bacterial or viral infections (4), or by acquisition of a new strain of a colonizing bacterium (1,2). Nonencapsulated or nontypeable Haemophilus influenzae (NTHi) can be isolated in up to 80 to 87% of COPD exacerbations (5,6) and is the most common bacteria colonizing the airways in COPD (6), with colonization correlated with exacerbations, severity of airway inflammation (5), and symptoms (2,6).…”
mentioning
confidence: 99%
“…In further support of the vicious circle hypothesis, exacerbations of COPD in association with a new bacterial strain are associated with increases in systemic and local inflammatory mediators, including serum C-reactive protein and sputum TNF-a and neutrophil elastase. These increases were higher than those seen in exacerbations associated with preexisting bacteria or with pathogen-negative exacerbations (14).…”
Section: Infection In Copd: the Role Of Nontypeable H Influenzaementioning
confidence: 60%